2017
DOI: 10.1103/physrevb.96.085427
|View full text |Cite
|
Sign up to set email alerts
|

Combined spectroscopic and ab initio investigation of monolayer-range Cr oxides on Fe(001): The effect of ordered vacancy superstructure

Abstract: We investigated the electronic structure of an ultrathin Cr oxide film prepared by growing about 0.8 monolayers of Cr on the oxygen-terminated Fe(001)-p(1×1)O surface and characterized by the formation of an ordered array of Cr vacancies producing a ( √ 5× √ 5)R27• superstructure. We combined experimental techniques such as angle-and spin-resolved photoemission spectroscopy, low-energy electron diffraction, and scanning tunneling spectroscopy with ab initio calculations, focusing on (i) the peculiar energy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
4
9
0
Order By: Relevance
“…The two lowest panels show the antiferromagnetic alignment of Cr and Fe, while in the third one, the small spin polarization of oxygen atoms can be appreciated, as discussed in our earlier work. 16 Notably, the binding energy of the oxygenrelated features is in good agreement with the peak observed in the PES. The two upper panels of Fig.…”
Section: Journal Of Applied Physicssupporting
confidence: 75%
See 2 more Smart Citations
“…The two lowest panels show the antiferromagnetic alignment of Cr and Fe, while in the third one, the small spin polarization of oxygen atoms can be appreciated, as discussed in our earlier work. 16 Notably, the binding energy of the oxygenrelated features is in good agreement with the peak observed in the PES. The two upper panels of Fig.…”
Section: Journal Of Applied Physicssupporting
confidence: 75%
“…The latter, which is related to oxygen states, is reminiscent of a similar peak that characterizes the PES spectrum of the Fe(001)-p(1 Â 1)O substrate (not shown here) as discussed in Ref. 16.…”
Section: Journal Of Applied Physicssupporting
confidence: 62%
See 1 more Smart Citation
“…2(b)] is characterized by a sharp peak at about À4.3 eV due to photoemission from O 2p-derived states and some small intensity signal from bulk Fe 3d states close to the Fermi energy (E F ). 40,41 Two spin-resolved features are visible on the corresponding IPES spectrum [ Fig. 2(b)], due to transitions toward the bulk majority and minority-spin empty states.…”
mentioning
confidence: 99%
“…In recent works [14][15][16] some of us focused on the C 60 /Fe(001) interface, both on the experimental and theoretical viewpoint. We demonstrated that the induced magnetic properties on the molecules depend on the spin polarization of the substrate states interacting with the molecule itself and by their decay toward vacuum.…”
Section: Introductionmentioning
confidence: 99%